Anti-leukemia activity of a Hsp70 inhibitor and its hybrid molecules - Seong-Hyun Park (Nature Portfolio, 2017)
Abstract In this study we examined the anti-leukemia activity of a small molecule inhibitor of Hsp70 proteins, apoptozole (Az), and hybrids in which it is linked to an inhibitor of either Hsp90 (geldanamycin) or Abl kinase (imatinib). The results of NMR studies revealed that Az associates with an ATPase domain of Hsc70 and thus blocks ATP binding to the protein. Observations made in the cell study indicated that Az treatment promotes leukemia cell death by activating caspase-dependent apoptosis without affecting the caspase-independent apoptotic pathway. Importantly, the hybrids composed of Az and geldanamycin, which have high inhibitory activities towards both Hsp70 and Hsp90, exhibit enhanced anti-leukemia activity relative to the individual inhibitors. However, the Az and imatinib hybrids have weak inhibitory activities towards Hsp70 and Abl, and display lower cytotoxicity against leukemia cells compared to those of the individual constituents. The results of a mechanistic study showed that the active hybrid molecules promote leukemia cell death through a caspase-dependent apoptotic pathway. Taken together, the findings suggest that Hsp70 inhibitors as well as their hybrids can serve as potential anti-leukemia agents.